PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA PT. MANDIRI TUNAS FINANCE CABANG PEKANBARU - kurniawan, teuku reza (Eko dan Bisnis: Riau Economic and Business Review, 2020)
This research was conducted at PT. Mandiri Tunas Finance Pekanbaru Branch. The purpose of this study was to determine the Effect of Service Quality on Customer Satisfaction at PT Mandiri Tunas Finance Pekanbaru Branch. The population in this study was 2,390 customers. In this study sampling using Accidental Sampling techniques, which amounted to 96 customers. The data used are primary and secondary data with analysis using simple linear regression. The results showed Y = 14.820 + 1.035 and the t test showed that t arithmetic> from t table (18,471> 1,98552) this meant that Quality of Service had a significant effect on Customer Satisfaction of PT. Mandiri Tunas Finance Pekanbaru Branch. The influence of Service Quality on Customer Satisfaction is 78.4% while the remaining 21.6% is influenced by other variables.